Comparison of Propofol Alone with Admixture of Propofol and Thiopentone Sodium for Laryngeal Mask Airway Insertion in Paediatric Elective Surgery - Faiza Tabassum, Sahira Nawaz Khan, Tanzeela Firdous, Maham Rana, Anum Anwar, Amina Qayyum (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Laryngeal Mask Airway (LMA) is mostly used for the application of general anesthesia. Intravenous Propofol is still preferable for induction of anesthesia due to its favorable recovery profile and low incidence of side effects. Thiopentone sodium is also one of the most commonly used intravenous induction agent. Combination of Propofol and thiopentone sodium may be more is beneficial rather than propofol alone. So we conducted this study to find more effective method. Objective: To compare the outcome of combination of Thiopentone sodium with Propofol versus Propofol alone for the Laryngeal mask airway insertion in pediatric patients. Methodology: This “Randomized controlled trial” was done at the Department of Anesthesia, Jinnah Hospital, Lahore for 6 months i.e. from July 2021 to Dec 2021. 80 children were selected for surgery through Non-Probability, Consecutive Sampling. Randomization of patients into group A & B was done. Informed consent was obtained from parents. Intravenous induction agents were prepared, for Propofol group (A), propofol was mixed with lignocaine and for the combination group (B), Thiopentone was combined with propofol. A correct sized LMA was inserted. Excellent LMA insertion was assessed. Data was analyzed in SPSS. Excellent LMA insertion in both groups was analyzed using Chi Square test with p <0.05 as statistically significant. Results: The mean age of patients in our study was 8.29±3.16 years. In Propofol group, there were 28 males and 12 were females while in combination group, 22 patients were male and 18 patients were females. In Propofol group, 15 cases had LMA score 1, 17 had LMA score 2 and 8 had LMA score 3. In combination group, 25 cases had LMA score 1 and 15 had LMA score 2 but no one had LMA score 3. The difference was significant (p<0.05). In Propofol group, 15 cases had excellent outcome while in 25 cases, excellent outcome could not be achieved. In combination group, 25 cases had excellent outcome while in 15 cases, excellent outcome could not be achieved. The difference was significant (p<0.05). Conclusion: So it has been proved that combination of Propofol with thiopentone sodium is more effective for effective insertion of LMA in children instead of using porpofol alone.